Insights of microemulsions – A thermodynamic comprehension - Yalavarthi, Prasanna; Y, Prasanna; MV, Basaveswara; CR, Sundaresan (Jordan Journal of Pharmaceutical Sciences, 2021)
There is a resurgence of interest in the technological advances of liquid microdispersion formulations. Extensive research had carried on macroemulsions in the 1890’s. Several theories suggesting the method of formulation and stabilization have profoundly investigated by research. There has been an exciting evolution of the concepts of microemulsions. Microemulsions are homogenous, transparent, optically isotropic, thermodynamically stable systems of oil and water stabilized by surfactant and cosurfactants with a size range of 5 to 10 nm. Microemulsions have a huge role in chemical, food, oil refining and pharmaceutical industries. This review focuses on the background, classification, components, selection criteria for excipients, and theories of emulsification with emphasis on thermodynamic considerations, and the stability involving thermodynamic and kinetic facets in the spontaneous formation of microemulsions.